The Roles of Language and Communication in Transforming and Sustaining National Development in Nigeria - Iyanda Kamoru Ahmed (Emerging Trends in Languages, 2024)
The objective of this paper is to assess the roles of language and communication in transforming and sustaining national development in Nigeria. There is the need to educate the people on how to use language and communication skills to achieve peace. An attempt is also made to highlight the objectives of language and communication skills, the processes involved and the channels to use in communicating. The paper finally suggests ways forward. The issue of education and development cannot be discussed successfully without the language which serves as the medium of instruction. Any literate Nigerian must, of necessity not only be able to read and write in English language but also communicate effectively with it. Most of the school subjects provide the learner with information and experience of things and the world around him that promote his intellectual and mental development. Without a proper vocabulary to convey the thoughts, this will not be feasible. A look at the Nigerian society will show that a large percentage Nigerians occupying important positions of authority are literate. Appointments into government services, political positions and in recently traditional positions consider literacy as a prerequisite. Added to this is the realization that promotions and the ability to advance your career through national and international interaction and communication is lied to your education and in particular your ability to express yourself in good English.
Keywords: Language; Sustainability National Development; communication; mental development; transformation